An Analysis and Comparison of the Commercial Bank Competition Regimes in Lithuania and Denmark - Stanikunas, Rimantas; Sergijenkovas, Ivanas (Ekonomika, 2018)
[full article and abstract in English]The article itself is focused on the empirical researches that had challenged two different operational areas of the same entity, with a special emphasis on the challenges and opportunities for the banking segments of Lithuania and Denmark. The influencing factors of the banking sector within these two countries have been analyzed and compared. We have delved into the issue that the successful standing of a parent company within its home area of operations is not by default a guarantee of success for its foreign branch or subsidiary. The decisive factors for a successful competitive approach within the banking segment are compared on the national levels of Denmark and Lithuania.
Keywords: banks, banking competition